Pemetaan Analisis Jabatan dan Penilaian Kinerja sebagai Dasar Pengembangan Sistem Remunerasi - Hidayah, Nur; Dewi, Arlina (Universitas Muhammadiyah Yogyakarta, 2021)
Job analysis and performance appraisals are the basis of developing a remuneration system consisting of fees for position, fees for service, and fees for people. Clinic Pratama receives payment for health services for patients participating in the National Health Insurance in the form of a capitation package. The capitation package distribution has not been regulated based on the position value index and performance appraisal according to the performance indicators of each employee’s detailed job descriptions, responsibilities and authorities. The purpose of this community service activity is to develop a remuneration system which can then be implemented in KPF as a strategy in human resource management facing the era of National Health Insurance (JKN) to achieve Universal Health Coverage (UHC). The method used is a qualitative method through a Focus Group Discussion (FGD) approach, interviews and documentation studies. The results of community service show that the Remuneration System can be developed based on Job Analysis and Performance Appraisals